PENERAPAN ETIKA BISNIS ISLAM DALAM AKTIVITAS EKSPOR IMPOR DI PT ANUGERAH ALFA LESTARI - Miftakhul Jannah; Abdul Haris Romdoni; Darmanto (Jurnal Ilmiah Ekonomi Islam, 2026)
This study examines the implementation of Islamic business ethics in export–import activities at PT Anugerah Alfa Lestari, an export-oriented manufacturing company operating within global trade networks. The increasing complexity of international business transactions requires companies to adopt ethical governance frameworks capable of ensuring transparency, accountability, and sustainability. While previous studies have predominantly focused on the application of Islamic business ethics in Islamic financial institutions and small enterprises, limited attention has been given to its implementation within international trade and export–import operations. This study employs a qualitative case study approach using in-depth interviews, observations, and documentation as data collection techniques. The collected data were analyzed through thematic analysis based on the principles of shidq (honesty), ‘adl (justice), and amanah (trustworthiness). The findings indicate that Islamic business ethics have been systematically integrated into the company’s operational practices through transparent contractual arrangements, equitable risk allocation, open communication, and responsible management of clients’ raw materials. Furthermore, the implementation of these ethical principles contributes to strengthening long-term business relationships, enhancing stakeholder trust, minimizing potential conflicts, and supporting operational sustainability. This study proposes a conceptual model that positions Islamic business ethics not merely as a moral guideline but as a strategic governance framework capable of supporting sustainable business performance within global value chains.